2022
DOI: 10.3390/cancers14205055
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics by NMR Combined with Machine Learning to Predict Neoadjuvant Chemotherapy Response for Breast Cancer

Abstract: Neoadjuvant chemotherapy (NACT) is offered to patients with operable or inoperable breast cancer (BC) to downstage the disease. Clinical responses to NACT may vary depending on a few known clinical and biological features, but the diversity of responses to NACT is not fully understood. In this study, 80 women had their metabolite profiles of pre-treatment sera analyzed for potential NACT response biomarker candidates in combination with immunohistochemical parameters using Nuclear Magnetic Resonance (NMR). Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…Various studies have documented changes in amino acid levels in breast cancer. For instance, prior research indicated a correlation between proline and resistance to neoadjuvant chemotherapy in breast cancer [31]. Additionally, higher levels of arginine were observed in breast cancer patients resistant to treatment compared to those who were sensitive [31,32], and elevated levels of isoleucine were linked to pCR, as con rmed by this study [33].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Various studies have documented changes in amino acid levels in breast cancer. For instance, prior research indicated a correlation between proline and resistance to neoadjuvant chemotherapy in breast cancer [31]. Additionally, higher levels of arginine were observed in breast cancer patients resistant to treatment compared to those who were sensitive [31,32], and elevated levels of isoleucine were linked to pCR, as con rmed by this study [33].…”
Section: Discussionsupporting
confidence: 74%
“…For instance, prior research indicated a correlation between proline and resistance to neoadjuvant chemotherapy in breast cancer [31]. Additionally, higher levels of arginine were observed in breast cancer patients resistant to treatment compared to those who were sensitive [31,32], and elevated levels of isoleucine were linked to pCR, as con rmed by this study [33]. The metabolic pathway involving glycine, serine, and threonine has been associated with breast cancer invasion [34] and may serve as a predictor for the response to neoadjuvant chemotherapy, particularly in triple-negative breast cancer [25].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, leucine, HR− and HER2+ are directly related to NATC sensitivity. In addition, glyoxylate and dicarboxylate metabolism have been implicated in NATC resistance ( 149 ) ( Figure 3A ).…”
Section: Omics and Treatment Implicationsmentioning
confidence: 99%
“…The application of LASSO method already showed its utility in multiclass classification of cancer tissues for rapid diagnosis in intra-surgery settings upon integration with mass spectrometry ( 20 , 22 , 23 ). Recently, LASSO showed good performances in classifying biological samples based on the molecular information captured by NMR ( 24 26 ). Note that this parsimonious method is less susceptible to the noise linked to the heterogeneity of the samples ( 27 ).…”
Section: Introductionmentioning
confidence: 99%